Restoring plant and insect community diversity in a crested wheatgrass dominated area - Abubaira, Mabruka H., author; Paschke, Mark W., advisor; Meiman, Paul, advisor; Brown, Cynthia S., committee member; Shahba, Mohamed A., committee member; Jonas, Jayne L., committee member (Colorado State University. Libraries, 2019)
Changing climate and plant invasion are having negative impacts on biodiversity in rangeland ecosystems. Crested wheatgrass (Agropyron cristatum [L.] Gaertn.), a nonnative species, has been used to improve livestock forage on rangelands. However, this nonindigenous species can result in reduced native plant diversity. I conducted a study to determine the most successful native plants (southern, central, or northern US ecotypes) for use in restoration of crested wheatgrass stands and to examine if increased seed rain of forbs and shrubs will result in increased establishment of these life forms. In Fall 2012, I seeded a mix of native plants in a completely randomized design in Larimer County, CO. I tested 6 seed mix treatments containing southern, central, or northern US ecotypes: grass only, grass and forb, grass and shrub, grass, forb and shrub, or grass with bird perches to provide a natural source of seed rain, and unseeded controls. I sampled aerial cover of seeded and unseeded plants from 2013-2015. In each year, I observed native plants from southern areas had more cover than native plants from northern areas. Promoting seed rain via bird perches had no effect on forb and shrub cover. I found a high cover of non-native forbs in plots seeded with grass only. Establishing native plants in degraded rangelands is an important approach for restoring community diversity, and using ecotypes adapted to future conditions may help improve seeding success. Also, declines in plant species diversity led to decreases in insect diversity. In my study, I proposed that greater plant diversity would increase the number of herbivorous insects because insect communities depend on the availability of plants as basic resources for their growth. To examine the effects of plant richness on insect richness and abundance I sampled the insects by using three different techniques (drop trap, pitfall trap and pan trap) from the original restoration vegetation study. My results in this experimental study show that plant richness did not support the total number of insects. The total abundance of all insects did not differ significantly across treatments from data collected by pitfall trap and pan trap techniques. However, the order Homoptera was the most abundant group found in the verity of plant species treatment (n=15) from drop-trap data.
Keywords: bird birches; plant invasion; seed mix; crested wheatgrass; biodiversity; restoration